Integrating mindfulness and connection practices into preservice teacher education improves classroom practices. (April 2020) - Hirshberg, Matthew J.; Flook, Lisa; Enright, Robert D.; Davidson, Richard J.
Abstract: Teachers vary in their ability to enact effective teaching practices. We randomly assigned 88 early education preservice teachers to standard teacher education or teacher education plus a 9-week mindfulness-based intervention. Using the Classroom Assessment Scoring System (CLASS) as our primary outcome, we assessed effective teaching practices at baseline and at a 6-month follow-up that occurred during full-time student teaching. Mindfulness, negative affect, and well-being were assessed at baseline, post-test, and follow-up. At follow-up, we observed significant GROUP × time interactions on all major CLASS domains: Instructional supports, Emotional supports, and Classroom organization favoring the intervention group (Cohen's d 's 0.53–0.65). Daily mindfulness practice was significantly associated with intervention group improvements on Instructional supports ( r = .39) and Classroom organization ( r = .38). No group differences were observed on negative affect or well-being. Implications for teacher education are discussed. Highlights: Teachers do not always put into practice what they know. Mindfulness training improved preservice teachers' ability to observe experience. Mindfulness training enhanced preservice teacher classroom management behaviors. Integrating mindfulness and connection practices into teacher education may improve outcomes.